THE SCARLET LETTER - HAWTHORNE, NATHANIEL (London, UK HarperCollins Publishers, 2010)
In Puritan, 17th century Boston, Hester Prynne is an independent-minded woman who stands alone against society. Having given birth to a child after an illicit affair, she refuses to name the father and is forced to the wear the letter "A" (representing "adulteress) embroidered on her dress.
Keywords: English - Fiction